[RETRACTED] IMPACT PSYCHOLOGICAL AND PSYCHO-PHYSICAL WORK DISTRESS ON TOOTH MOBILITY IN RAT MODEL (ARTICLE RETRACTED FROM IBSC PROCEEDING) - Zahreni Hamzah; Suhartono Taat Putra; Elyana Asnar STP (UNEJ e-Proceeding, 2016)
Retracted under author request.